Use of Space and Safety Perceptions from a Gender Perspective: University Campus, Student Lodging, and Leisure Spots in Concepción (Chile) - José Prada-Trigo; Paula Quijada; Gabriela Varela (Social Sciences)
This paper explores the different perceptions of safety of male and female university students, analyzing the gendered construction of space across three key settings of student life. The study employs a qualitative methodology based on 20 in-depth interviews conducted with both male and female students on the main campus of the Universidad de Concepción (Chile). The results show that female students adopt avoidance and precautionary strategies when navigating university and leisure spaces. These strategies limit their freedom of movement and contrast with the more unconstrained spatial behaviors reported by male students. The findings also reveal a perceived loss of safety as spaces become more communal and less private, particularly for female participants. This research underscores the need to better understand how gendered perceptions of safety shape everyday spatial practices within academic environments.